Autophagy inhibitors 3-MA and LY294002 repress osteoclastogenesis and titanium particle-stimulated osteolysis. (30th May 2021) - Chen, Weishen; Xian, Guoyan; Gu, Minghui; Pan, Baiqi; Wu, Xiaoyu; Ye, Yongyu; Zheng, Linli; Zhang, Ziji; Sheng, Puyi
Abstract : In this study, we found autophagy inhibitors 3-MA and LY294002 reduced osteoclast differentiation and osteoclast-related genes in vitro . In vivo, 3-MA and LY294002 repressed titanium particle-stimulated inflammatory osteolysis and osteoclastogenesis. Abstract : Aseptic loosening caused by peri-implant osteolysis (PIO) is a common complication after joint replacement, and there is still no better treatment than revision surgery. The wear particle-induced inflammation response, especially subsequent osteoclastic bone resorption, is responsible for PIO. As the importance of wear particles in inducing autophagy in cells around the prosthesis in PIO has been discovered, this might be a central process underlying aseptic loosening. However, the role of autophagy induced by wear particles in osteoclastogenesis during PIO remains unclear. In this study, we investigated the role of autophagy in osteoclastogenesis and verified it in a mouse calvarial osteolysis model. We found that osteoclasts were increased in the interface membranes of patients with aseptic loosening. In vitro, knocking down the Atg5 gene or using autophagy inhibitors (3-MA, LY294002) to inhibit autophagy was found to repress osteoclastogenesis and decrease expression of the osteoclast-related genes TRAP, cathepsin K, and matrix metalloprotein 9 ( MMP-9 ) with or without titanium (Ti) particles. In vivo, 3-MA and LY294002 repressed Ti particle-stimulated osteolysis and osteoclastogenesis and reduced expression of the pro-inflammatory factors TNF-α, IL-1β, and IL-6. Our results suggest that 3-MA and LY294002 might be the potential medicines to prevent and treat PIO and aseptic loosening.